USE OF MYCOPHENOLATE MOPHETYL IN PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSUS - S.I. Valiyeva; E.I. Alexeeva; A.E. Aleksandrov; A.E. Dobrovolsky ("Paediatrician" Publishers LLC, 2006)
The article reports a case of highly active SLE and lupusbnephritis in a 15 years old boy, who was treated with mycophenolate mophetyl the case was notable for high activity and aggressive course of the disease with rapid development of renal unsufficiency, polyorganic unsufficiency and antiphospholipid syndrome. Although the patient received an appropriate active therapy, including synchronized therapy (consisting of timebrelated plasmopherresis and infusions of cyclophosphamide and metyl prednisolone), glucocorticoides, preparations improving blood circulation (pentoxyphillin, dipiridamol, heparine), intravenous immunoglobulins, the disease activity control was unsufficient. The administration of mycophenolate mophetyl has led to diminuition of the disease activity, which was registered at the end of the second week of treatment, and finally has reached a level of clinical and laboratoty remission of the disease.Key words: systemic lupus erythematosus, mycophenolate mophetyl, children, treatment.